Retention of physiology knowledge among medical students in basic science: a cross-sectional study - Hadad, Mohammad Khaksari; Dehghani, Mahmoud Reza; Okhovati, Maryam; Shafian, Sara (BMC medical education, 2025)
Background Medical educationists are concerned that the retention of basic science concepts weakens beyond the early years of medical programs, with clinicians rarely using basic sciences in clinical practice. This study was conducted to evaluate the knowledge retention of physiology courses in medical students at Kerman University of Medical Sciences. Methods This is a cross-sectional study at Kerman University of Medical Sciences. A retention test was conducted in physiology courses using multiple-choice questions. This study included 104 medical students who had completed their basic science courses. The students were in physiopathology, internship, and clerkship were selected. The mean and standard deviation were applied to analyze the data, and a two-sample t-test, one-way ANOVA, was performed with a significance level of P -value < 0.05. Results The results of this study in retention test scores showed that lost knowledge was revealed throughout the years. Additionally, the results showed that in three subjects—gastrointestinal, nervous system, and respiratory—the scores of students in Y1 were higher than those of students in other years. In the course of endocrinology, the highest mean score belonged to the students who entered medical school in Y4, and the difference in mean scores among the different groups was statistically significant ( P < 0.001). The mean scores in the urinary system course achieved by the medical students are presented, with students who entered medical school in Y3 having the highest mean scores compared to those in other years. Conclusions The key takeaway is that knowledge retention is not passive; it requires active reinforcement through educational strategies. By prioritizing active learning, integrating clinical relevance, and leveraging strategies like retrieval practice and spaced learning, medical educators can enhance long-term retention and better prepare students for clinical practice.